2013
DOI: 10.1001/jamainternmed.2013.2737
|View full text |Cite
|
Sign up to set email alerts
|

Association of Oral Glucocorticoid Use With an Increased Risk of Acute Pancreatitis

Abstract: Importance: Oral glucocorticoid use has been suggested to cause acute pancreatitis in several case reports. However, no epidemiological study has investigated this association. Objective: To conduct a nationwide population-based case-control study to investigate the potential association between oral glucocorticoid use and acute pancreatitis. Design: In this population-based case-control study, all individuals aged 40 to 84 years who developed a first episode of acute pancreatitis between 2006 and 2008 in Swed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 33 publications
(37 reference statements)
0
56
0
2
Order By: Relevance
“…Cause and effect of this ominous triad are discussed controversially but they seem to be linked in a multidirectional relationship. A recent Swedish nationwide case–control study showed increased risk for acute pancreatitis in patients under oral CS 11. The mechanisms by which CS induce pancreatitis are not yet fully elucidated 10.…”
Section: Discussionmentioning
confidence: 99%
“…Cause and effect of this ominous triad are discussed controversially but they seem to be linked in a multidirectional relationship. A recent Swedish nationwide case–control study showed increased risk for acute pancreatitis in patients under oral CS 11. The mechanisms by which CS induce pancreatitis are not yet fully elucidated 10.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with PLT platelet steroids and intravenous pulse methylprednisolone when necessary, combined with immunosuppressive agents, is recommended to block cytokine-induced inflammation and improve organ perfusion [18]. However, some studies have reported an association between glucocorticoid use and an increased risk of AP with unclear pathogenic mechanisms [19], which manifests as an increase in serum amylase level during the first few days of treatment. However, in our cohort, there was no significant difference between serum amylase levels, or in immunosuppressive agents and pulse steroid therapy between CP and AP, or between SAP and MAP patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathophysiological mechanism behind corticosteroid-induced pancreatitis remains unclear, recent data suggest it may be related to the systemic effects of these medications, and specific alterations of lipid and calcium metabolism in pancreatic cells 4. The current literature on epidemiological incidence of oral corticosteroid use suggests that the risk of acute pancreatitis was increased among current users compared with non-users, and the risk for development of this condition was highest 4–14 days after the medication was taken 3. This well-described period when acute onset of pancreatitis likely manifests is important for physicians to be aware of when a patient presents with the clinical symptoms of this disease and with recent history of corticosteroid use.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive case reports have described pancreatic anomalies in systemic diseases that require high dosage of oral chronic steroid regiments for treatment or remission. Such conditions, which require the aforementioned glucocorticoid therapy and have documented pancreatitis, include, but are not limited to, systemic lupus erythaematous, inflammatory bowel disease, IgA nephropathy and Wegener's granulomatosis 3. Although the exact dosage of corticosteroid medication to elicit pancreatic damage has not been established, review of reported incidents of drug-induced pancreatitis reveal that these are after significantly high doses of medication.…”
Section: Introductionmentioning
confidence: 99%